A Simple Synthetic Method of a 1, 3, 5‐Triazine UV Absorbent CGL‐479 and Its Characterization. (20th May 2014) - Li, Lei; Mang, You; Jin, Di; Chen, Li‐gong
<x xml:space="preserve">Abstract</x> As a novel ultraviolet (UV) absorbent with excellent performance in UVA section (320 400 nm), 2‐2‐hydroxy‐4‐[(octyloxycarbonyl)ethylideneoxy]phenyl‐4, 6‐Bis(4‐biphenylyl)‐1, 3, 5‐triazine (CGL‐479) was synthesized in a simple method with a total yield of 45.3% in four steps. Its outstanding UV absorption capability (λmax = 326 nm, εmax = 4.15 × 104 Lmol−1cm−1), high thermostability [T5 (the temperature of losing 5% in weight) = 385 °C], and compatibility with polymer materials make it a potential substitute of the traditional UV absorbents.